Recreating the Bone Marrow Microenvironment to Model Leukemic Stem Cell Quiescence - O’Reilly, Eimear; Zeinabad, Hojjat Alizadeh; Nolan, Caoimhe; Sefy, Jamileh; Williams, Thomas; Tarunina, Marina; Hernandez, Diana; Choo, Yen; Szegezdi, Eva (Frontiers in Cell and Developmental Biology, 2021)
The main challenge in the treatment of acute myeloid leukaemia (AML) is relapse as it has no good treatment options and 90% of relapsed patients die as a result. It is now well accepted that relapse is due to a persisting subset of AML cells known as leukaemia-initiating cells or leukemic stem cells (LSCs). Haematopoietic stem cells (HSCs) reside in the bone marrow microenvironment (BMM), a specialised niche that co-ordinates HSC self-renewal, proliferation and differentiation. HSCs are divided into two types, long-term HSCs (LT-HSCs) and short-term HSCs (ST-HSCs) where LT-HSCs are typically quiescent and act as a reserve of HSCs. Like LT-HSCs, a quiescent population of LSCs also exist. Like LT-HSCs, quiescent LSCs have low metabolic activity, low RNA synthesis and receive pro-survival signals from the BMM, making them resistant to drugs and upon discontinuation of therapy, they can become activated and re-establish the disease. Several studies have shown that activation of quiescent LSCs may sensitise them to cytotoxic drugs. However, it is very difficult to experimentally model the quiescence-inducing bone marrow microenvironment (BMM). Here we report that culturing AML cells with bone marrow stromal cells, transforming growth factor beta-1 and hypoxia in a three-dimensional system can replicate the quiescence-driving BMM. A quiescent-like state of the AML cells was confirmed by reduced cell proliferation, increased percentage of cells in the G0 cell cycle phase and a decrease in absolute cell numbers, expression of markers of quiescence and reduced metabolic activity. Furthermore, the culture can be established as co-axial microbeads enabling high-throughput screening to which has been used to identify combination drug treatments that can break BMM-mediated LSC quiescence enabling the eradication of quiescent LSCs.